Effect of asparagine, corncob biochar and Fe(II) on anaerobic biological treatment under low temperature: Enhanced performance and microbial community dynamic. (1st September 2022) - Li, Xinjuan; Qin, Ronghua; Yang, Wenjing; Su, Chengyuan; Luo, Zehua; Zhou, Yijie; Lin, Xiangfeng; Lu, Yingqi
Abstract: To ensure the efficiency of anaerobic biological treatment technology at lower temperature will expand the application of anaerobic reactor in practical industrial wastewater treatment. Through a batch experiment, asparagine, corncob biochar and Fe 2+ were selected as strengthening measures to analyze the effects on the anaerobic sludge characteristics, microbial community and functional genes in the low temperature (15 °C). Results showed that after 21 days, asparagine began to promote chemical oxygen demand (COD) removal by the anaerobic treatment, with highest COD removal rate (81.65%) observed when the asparagine concentration was 1 mmol/L. When adding 3 g biochar, 25 mg/L Fe 2+, and the combination of biochar and Fe 2+, the COD removal rates reached to 82%, 92% and 97%, respectively. In the presence of asparagine, both biochar and Fe 2+ alone or in combination increased the activity of protease (16.35%–120.71%) and coenzyme F420 (5.63%–130.2%). The relative abundance of Proteobacteria and Methanobacterium increased in the presence of biochar and Fe 2+ . In addition, the KEGG results showed that the combined addition of biochar and Fe 2+ enhanced bacterial replication and repair and promoted amino acid metabolism of archaea. Graphical abstract: Image 1 Highlights: Strengthening of a low-temperature anaerobic treatment process was evaluated. Asparagine began to promote COD removal at asparagine 1 mmol/L. Biochar and Fe(II) increased the activity of protease and coenzyme F420 . Biochar and Fe(II) enhanced bacterial amino acid metabolism.